Features of development of species of the genus Veronica L. in the conditions of steppe zone of Ukraine - Chypyliak, Tetiana; Zubrovska, Olha (Hacquetia, 2021)
The paper deals with peculiar features of development of the species Veronica austriaca ssp. teucrium L., V. incana L. and V. prostrata L. in the conditions of the steppe zone of Ukraine (central part of the country). Under the action of climatic changes occurring for the last 20 years, the species began to grow 6-14 days earlier and increased the vegetation period by 15-25 days. Flowering started at the usual time (late May too early June) and its duration changed only in V. prostrata (with the increase by almost 10 days). Under the effect of extreme growing conditions (hot weather and drought), phenotypic changes of parameters of the leaf blade were determined. Decrease in the area of the leaf blade by almost 2 times was recorded in V. prostrata and V. incana, whereas in V. austriaca ssp. teucrium it did not change significantly. Length and width of the leaf in V. prostrata and V. incana decreased by 20-30%, but in V. austriaca ssp. teucrium a decrease was observed for the leaf width only while its length increased by 17%. Analysis of correlation of climatic factors (air temperature, precipitation amount) to the morphometric parameters of the leaf during seasonal development showed greater dependence of their value on the air temperature, which was confirmed by the inverse correlation coefficients (r = -0.55–-0.66). In the unfavorable growing conditions, the features of formation of the underground part of species are manifested in the inhibited development of underground shoots (by 80-85%) and stimulation of branching and increase in the length of thin sucking roots (1.5 times). Studied species of the genus Veronica in the climatic conditions of the steppe zone of Ukraine go through all stages of phenological development and are marked by rather wide range of phenotypic changes in the vegetative sphere. The findings can be used for the development of techniques of growing and reproduction of veronicas in the arid conditions of cultivation.